2022
DOI: 10.1029/2022gl100852
|View full text |Cite
|
Sign up to set email alerts
|

Electric Discharge in Erupting Mud

Abstract: Self‐ignition during the explosive eruption of mud volcanoes can create flames that in some cases reach heights that exceed hundreds of meters. To study the controls on electrical discharge in natural mud, we performed laboratory experiments using a shock‐tube apparatus to simulate explosive eruptions of mud. We vary the water content of the mud and proportions of fine particles. We measure electric discharge within a Faraday cage and we use a high‐speed video camera to image the eruption of mud and some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…The Hunga Tonga‐Hunga Ha'apai (HTHH) volcano erupted on 15 January 2022 at approximately 04:15 UT after several days of increased geological activity (Pradipta et al., 2023; USGS, 2022). Previous studies have reported that the HTHH volcanic eruption caused multi‐layer linkage disturbances, including atmospheric disturbances, tsunamis, as well as anomalous variations in multiple physical quantities such as atmospheric pressure, temperature, ground and ionospheric electromagnetic fields (Briggs et al., 2022; D’Arcangelo et al., 2022; Podglajen et al., 2022; Poli & Shapiro, 2022; Rajesh et al., 2022; Springsklee et al., 2022; Wright et al., 2022). After the volcanic eruption, the generated Lamb waves propagated at the boundary of air and solid Earth, and traveled around the Earth several times (Amores et al., 2022; Lin et al., 2022; Omira et al., 2022; Otsuka, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The Hunga Tonga‐Hunga Ha'apai (HTHH) volcano erupted on 15 January 2022 at approximately 04:15 UT after several days of increased geological activity (Pradipta et al., 2023; USGS, 2022). Previous studies have reported that the HTHH volcanic eruption caused multi‐layer linkage disturbances, including atmospheric disturbances, tsunamis, as well as anomalous variations in multiple physical quantities such as atmospheric pressure, temperature, ground and ionospheric electromagnetic fields (Briggs et al., 2022; D’Arcangelo et al., 2022; Podglajen et al., 2022; Poli & Shapiro, 2022; Rajesh et al., 2022; Springsklee et al., 2022; Wright et al., 2022). After the volcanic eruption, the generated Lamb waves propagated at the boundary of air and solid Earth, and traveled around the Earth several times (Amores et al., 2022; Lin et al., 2022; Omira et al., 2022; Otsuka, 2022).…”
Section: Introductionmentioning
confidence: 99%